Dinamika Relasi Gender dan Eksklusi Sosial: Analisis Inklusivitas Pembangunan Desa di Niukbaun - Mariayani Oktafina Rene (Journal of Public Administration and Local Governance, 2026)
Women have the capacity to contribute to a variety of aspects of the development process. Nonetheless, there exists a potential disparity in women's responsibilities and involvement in development between urban and rural regions. The analysis of women's involvement in village development can be conducted by examining their access to and control over resources and development avenues. When women do not have enough access and control in the development process, they are potentially exposed to social exclusion at various phases of development. The goal of this study is to evaluate women's access, control and social exclusion in Niukbaun Village, Kupang Regency, in the context of development. The research was conducted using a qualitative approach. Data collection was carried out through observation, structured interviews with informants, and literature study. The analysis of the research results used the Harvard gender analysis model, which focuses on access and control, as well as an analysis of social exclusion that looks at the development process and the benefits received. The results of the study show that access to and control over resources are still dominated by men, particularly in their position as head of the family or successor to the clan. This condition is reinforced by gender-based division of labour, where women are more often placed in domestic roles as housewives, while agricultural land management and livestock activities are dominated by men. Strategic positions in village administration are mostly held by men, limiting women's opportunities to participate in decision-making processes. This limitation has resulted in women having minimal access and control in voicing their aspirations and interests in core village development programmes, which ultimately reinforces gender inequality in the context of rural development.